Radiation-induced undifferentiated pleomorphic sarcoma of the breast. Issue 2 (10th February 2020) - Kong, Joshua; Shahait, Awni D; Kim, Steve; Choi, Lydia
Abstract : Breast sarcoma is a rare form of malignancy that arises from connective tissue within the breast, comprising less than 5% of all sarcomas. They develop as primary tumours or as secondary following radiation therapy. Diagnosis can be challenging as breast sarcomas are often asymptomatic and resemble benign breast tissue changes. Radiation-induced breast sarcomas present in various forms with an average latency period of 10–20 years following initial radiation therapy. Angiosarcomas are the most common form, while other types such as undifferentiated pleomorphic sarcomas remain rare. Here, we report a case of radiation-induced undifferentiated pleomorphic breast sarcoma in a 75-year-old woman that developed nearly 20 years following breast conserving surgery and radiation for invasive ductal carcinoma. The patient initially noticed a mass in 2017 on self-examination. The mammogram, ultrasound and biopsy at the time showed a benign 2.2 cm nodular fasciitis without malignancy. The mass grew rapidly in the next 6 months to 5.6 cm and repeat biopsy diagnosed undifferentiated pleomorphic sarcoma. The mass abutted the pectoralis muscle but staging workup ruled out distant metastasis and the patient underwent wide local resection of the mass with clear margins. The patient subsequently underwent further postoperative radiation due to insufficient posterior margin width on wide local excision, as chest wall resection would have been required for a wider posterior margin. Prognosis for postradiation sarcomas is generally poor with 27%–36% 5-year survival, with surgical resection as the main line of treatment. The patient currently remains disease-free after 15 months of surveillance.